Loss of tubular creatinine secretion as the only sign of tubular proximal cell dysfunction in light chain proximal tubulopathy: A case report. Issue 26 (June 2016) - Stehlé, Thomas; Vignon, Marguerite; Flamant, Martin; Figueres, Marie-Lucile; Rabant, Marion; Rodenas, Anita; Noël, Laure-Hélène; Arnulf, Bertrand; Vidal-Petiot, Emmanuelle
Abstract : Abstract: Light chain proximal tubulopathy (LCPT) is a rare disease, characterized by cytoplasmic inclusions of light chain (usually kappa) immunoglobulins. Clinical presentation is usually a Fanconi syndrome. The proximal tubular dysfunction can be incomplete, and exceptional cases of LCPT without any tubular dysfunction have even been described. Here, we report a case of LCPT in which the only sign of proximal tubulopathy is the absence of secretion of creatinine, as assessed by the simultaneous measurement of renal clearance of creatinine and 51 CrEDTA. The loss of tubular creatinine secretion as a sign of tubular proximal cell dysfunction ought to be identified in patients with light chain proximal tubulopathy as it leads to a clinically relevant underestimation of GFR by the creatinine-derived equations. The prevalence and prognostic significance of this particular proximal tubular damage in LCPT remain to be determined.